Vertical diffusivity of the Western Arctic Ocean halocline. Issue 8 (12th August 2014) - Shaw, William J.; Stanton, Timothy P.
Abstract A nearly year‐long series of upper ocean temperature, conductivity, and temperature microstructure profiles were collected from an ice camp drifting in the Beaufort Gyre as part of the 1997–1998 Surface Heat Budget of the Arctic Experiment (SHEBA). Geographically, the record includes portions over the deep Canada Basin and the steep bathymetry of the Chukchi Borderlands region. Hydrographically, the record includes "cool, " Pacific‐origin haloclines, which contain a variety of subsurface temperature maxima, and cold haloclines typical of the Eurasian Basins. We present estimates of the vertical turbulent diffusivity derived from the dissipation rate of thermal variance and calculations of the associated vertical heat fluxes. We find that vertical diffusion proceeds at molecular rates in the deep basins and away from topographic features. While still relatively small, diffusivity is enhanced by 1 order of magnitude near and above the Chukchi Borderlands. The enhanced diffusivity is correlated to an increase in water column strain variance above the Borderlands, providing a linkage between bathymetry, internal wave activity and turbulence. The Chukchi Borderlands play a significant role in heat transport in the Western Arctic. They are a pathway for horizontal heat transport and a hot spot for vertical heat transport. Vertical fluxes make a substantial contribution to the energy balance of the sea ice cover in this region. Heat fluxes between the halocline and underlying Atlantic Water are shown to be small and lacking vertical connection near surface waters.